2022
DOI: 10.1155/2022/2136464
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vehicle Dynamic Response from Track Irregularity Using Deep Learning Techniques

Abstract: To improve the quality of track maintenance work, it is a desire to estimate vehicle dynamic behavior from track geometry irregularities. This paper proposes a deep learning model to predict vehicle responses (e.g., vertical wheel-rail forces, wheel unloading rate, and car body vertical acceleration) using deep learning techniques. In the proposed CA-CNN-MUSE model, convolutional neural networks (CNNs) are used to learn features of track irregularities, and multiscale self-attention mechanisms (MUSE) are emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, during the actual operation of high-speed trains, the axle box bearings of high-speed trains are coupled with other components, which will be subject to various external excitations, among them, wheel-rail excitation is the main source of vibration acceleration experienced by various components of the train. Such as wheel polygon [28][29][30][31][32], wheel flat scar [33][34][35], track irregularity [2,33,36,41], etc. Based on the multi-body dynamics theory, the literature [29] established a rigid-flexible coupling dynamic model of vehicle-track, analyzed the influence of polygon amplitude on the time-frequency domain of wheel noise, and the research results showed that when the polygon order is 20, with the increase of polygon amplitude, the wheel-rail vertical force and the acceleration of wheel-rail and rail plate gradually increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the actual operation of high-speed trains, the axle box bearings of high-speed trains are coupled with other components, which will be subject to various external excitations, among them, wheel-rail excitation is the main source of vibration acceleration experienced by various components of the train. Such as wheel polygon [28][29][30][31][32], wheel flat scar [33][34][35], track irregularity [2,33,36,41], etc. Based on the multi-body dynamics theory, the literature [29] established a rigid-flexible coupling dynamic model of vehicle-track, analyzed the influence of polygon amplitude on the time-frequency domain of wheel noise, and the research results showed that when the polygon order is 20, with the increase of polygon amplitude, the wheel-rail vertical force and the acceleration of wheel-rail and rail plate gradually increased.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, deep learning-related technologies have flourished [37][38][39][40] and have gradually been applied to the field of model analysis. The literature [41] proposed a deep learning model that uses deep learning technology to predict the vehicle response under track irregularities. The model successfully simulated the vertical wheel-rail force and body acceleration, but the estimation of lateral wheel-rail force and body acceleration is not as good as the results for vertical wheel-rail force.…”
Section: Introductionmentioning
confidence: 99%